2021
DOI: 10.5897/jeif2021.1127
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interest rate on economic growth: Further insights from the Gambia

Abstract: The main objective of this paper is to examine the effects of interest rate on economic growth in Gambia over the period 1993 to 2017. The Vector E rror Correction Model (VECM) is used to check the relationships between the dependent variable (Gross Domestic Product) and independent variables (Real Effective Exchange Rate and Real Interest Rate), both in the short-run and long-run. Post estimation tests, including Lagrange Multiplier test for residual autocorrelation were also conducted for autocorrelation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…There is a long-run relationship between economic growth and inflation in Ind onesia, Singapore, Thailand, and the Philippines, except Malaysia; this result does not vary from the recent studies (see (Karahan & Colak, 2020;Rehman, Cismas, & Milin, 2022;Sinha, 2022)). A long-run relationship is detected between economic growth and interest rates in all countries, consistent with recent studies (see (Njie & Badjie, 2021;Oroud et al, 2023)). Economic growth and exchange rate also have a long-term relationship in Indonesia, Singapore, and Thailand; this result is similar to the findings obtained by Mawutor et al (2023).…”
Section: Resultssupporting
confidence: 91%
“…There is a long-run relationship between economic growth and inflation in Ind onesia, Singapore, Thailand, and the Philippines, except Malaysia; this result does not vary from the recent studies (see (Karahan & Colak, 2020;Rehman, Cismas, & Milin, 2022;Sinha, 2022)). A long-run relationship is detected between economic growth and interest rates in all countries, consistent with recent studies (see (Njie & Badjie, 2021;Oroud et al, 2023)). Economic growth and exchange rate also have a long-term relationship in Indonesia, Singapore, and Thailand; this result is similar to the findings obtained by Mawutor et al (2023).…”
Section: Resultssupporting
confidence: 91%
“…As argued by Njie and Badjie (2021), the preferable model for the assessment of the determinants of public debt is the vector error correction model (VECM) because the time series vary and are not stationary at the level term. However, the data are mostly stationary.…”
Section: Model Specificationmentioning
confidence: 99%
“…However, Mushtaq and Siddiqui (2016) presented an alternative perspective, suggesting that interest rates actually foster economic growth. In a recent study conducted by Matarr and Momodou (2021), has shown that there is no significant impact of interest rates on economic growth. According to recent studies conducted by Ukangwa and Ikechi (2022), Egbujor (2012), and Godwin and Sergius (2021), it has been suggested that the exchange rate has a detrimental impact on economic growth.…”
Section: Introductionmentioning
confidence: 99%